Oxygen stable isotope analyses on ameghinomya antiqua shells: A promising tool for palaeoenvironmental reconstruction along the quaternary patagonian Argentina coast? - Boretto, Gabriella Margherita (2019)
There are only a few data concerning the Quaternary climate fluctuations in the marine environments of the Atlantic Patagonian coast. In this regard, the aragonitic shell of the Ameghinomya antiqua bivalve offers the possibility to study the climate variability and the seasonal cycles of sea water temperature in the region at different geological times. We compared oxygen isotopic profiles along the shell-growth axis on four well-preserved A. antiqua bivalves collected from marine coastal deposits of Marine Isotope Stage (MIS) 7, MIS 5, Holocene (7.284 ±140 yr cal BP), and from the present-day active beach of Bahia Bustamante (Patagonia Argentina). Shell ontogeny was determined through the annual growth lines recorded along the external region of the shell, and was also verified by cross-section analyses. The fossil bivalves were around 15 years old, while the Present day shell was 10 years old. When the modern climatic data available are compared, the higher δ18Oshell values represent the cold season, while the lower δ18Oshell values indicate the warm season. The δ18Oshell ranges indicate different environmental conditions and seasonal temperature variations between specimens. By assuming, a constant δ18Ow calculated with the limited environmental data available, superficial seawater temperatures are estimated from the specimens. These paleotemperatures may overestimate water temperatures, and shell formation seems to occur with an offset from expected oxygen isotopic equilibrium with the water in which they lived. Meanwhile, A. antiqua shells are suitable bioarchives for the comparison of seasonal patterns throughout the Quaternary, thus constituting another proxy for the evaluation of paleoclimatic and paleoenvironmental changes in the Patagonia region.